Coordination-controlled single-atom tungsten as a non-3d-metal oxygen reduction reaction electrocatalyst with ultrahigh mass activity. (June 2019) - Chen, Zhigang; Gong, Wenbin; Liu, Zhibo; Cong, Shan; Zheng, Zuhui; Wang, Zhen; Zhang, Wei; Ma, Jingyuan; Yu, Haisheng; Li, Guihang; Lu, Weibang; Ren, Wencai; et al.
Abstract: Transition metal-nitrogen-carbon (M-N-C) catalysts have emerged as the most promising alternatives to their costly platinum–based counterparts for oxygen reduction reaction (ORR) catalysis, which are critical to renewable energy conversion and storage technologies. However, thus far, only 3d transition metals (Co, Fe, Ni, Mn, etc.) have often been good choices for the metal elements in such M-N-C catalysts, while other non-3d transition metals-based catalysts such as 5d tungsten (W) usually afford much inferior ORR activities in both bulk and nanoparticle form. Here, we report the atomically dispersed tungsten on nitrogen-doped carbon nanosheets with controlled W-N coordination numbers as efficient catalysts for ORRs, which are only formed through the deliberate modulation of the synthesis parameters, such as the pyrolysis atmosphere, temperature, and time, within a very narrow range. Instead of being considered to be almost inactive towards ORR, the single-atom tungsten electrocatalysts show remarkable, durable and coordination number-sensitive ORR catalytic ability. It is shown that single-atom tungsten with a W-N coordination number of 5 exhibits markedly high ORR catalytic activity in 0.1 M KOH with onset potential (∼1.01 V), half-wave potential (0.88 V) and a mass activity of 0.63 A/mg (at 0.9 V versus RHE), which even surpasses those of commercial Pt/C. Meanwhile, the WN5 catalyst catalyzes the ORR with a onset potential of 0.87 V and a half-wave potential of 0.77V in 0.1 M HClO4, both of which are nearly comparable to the benchmark Pt/C. In contrast, the single-atom tungsten electrocatalysts with W-N coordination numbers of 3 and 4 exhibit relatively poor ORR activity in both acidic and alkaline electrolytes. The DFT calculations suggest that the sharp increase in the ORR activity of the single-atom tungsten catalysts can be attributed to the moderate interaction between OH- and the single W atoms, which is probably caused by the optimal dz 2 -pz orbital hybridization and re-distribution of the charges. Graphical abstract: Coordination-controlled single-atom tungsten is demonstrated to show remarkable, durable, and coordination number-sensitive ORR catalytic ability, in deep contrast with other ORR-inert tungsten-based catalysts. More surprisingly, the single-atom tungsten catalyst can reach the top of the activity volcano, which even surpasses that of noble metal Pt.Image 1 Highlights: Atomically dispersed 5d tungsten with controlled W-N coordination numbers can serve as a remarkable and durable catalyst for ORR in both acidic and alkaline solution, in deep contrast with other ORR-inert tungsten-based catalysts. Single-atom tungsten with a W-N coordination number of 5 exhibits markedly high ORR catalytic activity with onset potential (∼1.01 V), half-wave potential (0.88 V), and a mass activity of 0.69 A/mg (at 0.9 V versus RHE), which even surpasses those of commercial Pt/C. The calculated UL value of our WN5 sample reaches as high as 0.85 V, which obviously surpasses that of noble metal Pt (0.76 V).